Keadilan , Diskriminasi Dan Sistem Perpajakan Terhadap Penggelapan Pajak - Djenni Sasmit; Kimsen (Jurnal Akuntansi Publik Nusantara, 2023)
This study aims to determine the effect of justice on tax evasion, to determine the effect ofdiscrimination on tax evasion, and the effect of the taxation system on tax evasion. The results of thisstudy are expected to be useful for the tax office and used as input and consideration inunderstanding the effect of justice, discrimination and taxation system on taxpayers' perceptions ofthe ethics of tax evasion. The research method used is qualitative research where the research aimsto determine the effect of the independent variable on the dependent variable. The analyticalmethod used is descriptive analysis, instrument test, classical assumption test, hypothesis test andmultiple linear equation test. The instrument used is a questionnaire. Based on research anddiscussion on justice, discrimination, and the tax system against tax evasion. Taxpayers' perceptionsof justice, discrimination, and the taxation system together have an effect on tax evasion. This isevidenced by the results of the significance value of the F test of 0.000 which is smaller than 0.05.This means that the better or not the perception of taxpayers regarding justice, discrimination, andthe tax system, it will affect the practice of tax evasion in the Tangerang area